Avaliação do efeito da risperidona e do aripiprazol sobre o comportamento tipo-autista e parâmetros oxidativos em ratos jovens: estudo pré-clinico - Medeiros, Caroline Liana Menschhein (2019)
Autistic Spectrum Disorder is a neurodevelopmental disorder with varying degrees of impairment in individuals. Social comununication deficits and the presence of restricted and repetitive behavioral patterns are essential for the diagnosis. Etiological factors such as neuroinflammation and oxidative stress in the Central Nervous System may be involved in its pathophysiology. The rising prevalence increases concern for the scientific community and drives studies, including the therapeutic possibilities for behavioral improvement. Objective: To evaluate the effects of risperidone and aripiprazole use on behavioral parameters and oxidative stress in an experimental autism model. Methods: To induce the animal model of autism, maternal immune activation was performed using LPS. The offspring females were separated into two groups: autistic type and non-autistic type. Then, they were divided into groups according to the treatment they received: risperidone or aripiprazole or saline for 21 days. From PND 43 the animals were submitted to behavioral tests. Afterwards, they were referred for euthanasia and the brain structures (hippocampus and prefrontal cortex) dissected and the material sent for biochemical analysis of TBARS, protein carbonylation, SOD and CAT. Results: Maternal immune activation in offspring was confirmed by the smelling parameter of the social interaction test. Treatment with aripiprazole and risperidone was able to improve some behavioral patterns of social interaction and short-term memory, with a tendency for better outcomes with aripiprazole. Regarding the oxidative stress evaluated data, the results were not significant.